The impact of 3D, 4D, and 5D Building Information Modeling for reducing claims to service providers - Shanti Astri Noviani; Mawardi Amin; Sarwono Hardjomuljadi (SINERGI, 2022)
In construction, claims are usually a request for additional time, cost, or quality of work. A dispute will occur If the claim is not resolved correctly. In industrial revolution 4.0, we can use the Building Information Modeling (BIM) method to increase efficiency. BIM is a digital display containing all information about building elements integrated with the building's life cycle period. BIM will accelerate and reduce risks in construction, including the impact of claims. In Indonesia, several consultants/contractors have been implemented BIM in construction projects. This research aims to determine the effect of using 3D, 4D, and 5D BIM in construction projects for reducing claims to service providers as seen from the indicators on BIM 3D, 4D, 5D BIM. The research method used is a descriptive research method with a Q-method approach using closed survey research instruments to 37 contractor/consultant respondents who use BIM. The results obtained from the 3D BIM 4 indicators affect the reduction of claims. The 4D BIM indicator has two hands that affect the decrease in claims. The 5D BIM indicators all involve reducing claims.